THE EFFECT OF GENDER DIFFERENCES ON PRO ENVIRONMENTAL BEHAVIOR IN DIRECTORATE GENERAL BINAPENTA&PKK, MINISTRY OF MANPOWER, 2016 - Meyrina Pronityastuti (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2017)
The purpose of this research is to determine the effect of gender differences on pro environmental behavior among employees of Directorate General Binapenta and PKK, Ministry of Manpower. Samples of 126 respondents were taken by taking a simple random sampling technique from the employees. This research used non test instruments, measuring pro environmental behavior. The research results show that there were diffences of pro environmental behavior which affected by the gender.. Based on the result, the pro environmental behaviors of female employees are better than male employees. Therefore, in order to improve pro environmental behavior of employees, gender of the employees should be considered as influential factors.